The Determinants for Shopping Cart Abandonment - Yusuf, Leonardi Levino; Tamara, Dewi; Setiadi, Nugroho J. (Directorate of Academic Research and Community Services, 2021)
Purpose – The purpose of this paper is to analyze the determinant that leads to shopping cart abandonment. In this research determinant that writer use are perceived cost (PC), complicated checkout (CC), Entertainment Motivation (EM), Emotional Ambivalence (EA), Information Overload over the Product (IA). Design/methodology/approach – A quantitative study was conducted, using a sample of 117 respondent consist of men and women who have ever done shopping cart abandonement. The hypotheses were tested by applying the Smart-PLS 3.2 software. Findings – The findings Perceived Cost (PC) has a positive and insignificant effect on shopping cart abandonment, Complicated Checkout (CC) has a positive and insignificant effect on shopping cart abandonment, Entertainment Motivation (EM) has a positive and significant effect on shopping cart abandonment, Emotional ambivalence (EA) has a positive and insignificant effect on shopping cart abandonment, meanwhile Information Overload (IO) has a positive and insignificant effect on shopping cart abandonment. From all the variable tested that has the most significant influence on shopping cart abandonment comes from Entertainment Motivation (EM).